Lens mass estimate in the Galactic Disk Extreme Parallax Microlensing event Gaia19dke - Maskoliunas, Marius; Kaczmarek, Zofia; Heidt, Jochen; Hundertmark, Markus; Tsapras, Yiannis; Wambsganß, Joachim (Acta astronomica, 2024)
We present the results of our analysis of Gaia19dke, an extraordinary microlensing event in the Cygnus constellation that the Gaia satellite discovered. This event featured a strong microlensing parallax effect, resulting in multiple light curve peaks. We conducted extensive photometric, spectroscopic, and high-resolution imaging follow-up observations to determine the mass and nature of the invisible lensing object. Using the Milky Way priors on the density and proper motion of lenses, we found that the lens is likely to be located at a distance of D-L = 3.3(-1.7)(+2.1) kpc, and has a mass of M-L = 0.50(-0.27)(+0.82) M-circle dot. Based on its low luminosity and mass, we propose that the lens in the Gaia19dke event is either a main sequence star or an isolated white dwarf. Due to its brightness, longevity, and lack of blending, Gaia19dke is a target for which the forthcoming Gaia Data Release 4 data will help to constrain the parameters of the lens.
Gesehen am 05.12.2025